The effect of Beauveria bassiana on Brazilian poplar moth Condylorrhiza vestigialis (Lepidoptera: Crambidae) - Dal Pogetta, Mario Henrique Ferreira do Amaral [UNESP]; Wilcken, Carlos Frederico [UNESP] (Polish Academy of Sciences Chancellery, 2012)
The Brazilian poplar moth is the most important pest of poplar plantations in Brazil. This research evaluated the effect of Beauveria bassiana Bals. (Vuill.) on the mortality and development of Condylorrhiza vestigialis Guen. (Lepidoptera: Crambidae). The aim was to develop alternative methods for management of this pest. The pathogens were sprayed on poplar leaves and .consequently, the pathogens reached the caterpillars. Bacillus thuringiensis var. kurstaki Berliner was sprayed as the standard treatment. The spray for the control was distilled water. Both pathogens B. bassiana and B. thuringiensis affected insect development with increase mortality at each stage of the insect cycle, reaching a satisfactory control level. Microbial control of Brazilian poplar moth with B. bassiana is promising. Tests with other strains and species of pathogens, mainly under field conditions, were also encouraging. This is the first report about the action of B. bassiana against C. vestigialis.